Changing the nature of the city: integrating phytoremediation for the future of Kansas City. - Mallinckrodt, Stephanie (Kansas State University, 2012)
There are six square miles of vacant land spread throughout Downtown Kansas City unkempt and untouched for the fear of what may exist in the soil, air, and water and the consequences that come with it (COR Team 2010, EPA 1997). Not developing the vacant/underutilized land causes more harm than good for the city, the locals, and the environment. It costs the city loss of tax revenue (Holt 2002). It hurts locals’ property values and possibly health. It inhibits the environment’s functions with potential toxins. By activating vacant/underutilized land through phytoremediation and redevelopment, it can meet the needs of the projected population growth in the next 30 years, accommodate the Rock Island Corridor, and dissolve any threats of contamination. With the threat of possible contamination on the vacant/underutilized land, surrounding properties, and industrial properties within the culturally rich Jazz and Crossroads districts downtown, phytoremediation is used as a continuation of the Rock Island Corridor’s linear park system and transit in the city context while allowing for redevelopment. The strategy examines regional to site specific strategies where phytoremediation is used to connect people to the environment, contain contaminant-producing places, and counteract contamination from new development. The development serves as a model for Kansas City to use the Rock Island Corridor to control site-specific problems as a catalyst for redevelopment of districts to solve large-scale issues through the use of phytoremediation. Phytoremediation allows for light contaminant production industries to remain functional and rely on phytoremediation to clean some of the waste to prevent excessive clean up in the future. With the help of the phytoremediation and development, it allows for us to understand how phytoremediation works while preventing sites from becoming vacant/underutilized urban areas for the betterment of the community as a proactive strategy to prevent brownfields. Phytoremediation supports sustainable preventative/remediation strategies while catering to community needs such as redevelopment along Rock Island Corridor and Common Line, multi-modal transit, Metrogreen, character of place, and city life. It blends site suitability with community needs, while creating a cleaner more efficient environment that is aesthetically appealing.
Keywords: urban design; phytoremediation; Rock Island Corridor; Kansas City; vacant/underutilized land; Area Planning and Development (0341); Design (0389); Sustainability (0640); Urban Planning (0999)